RADIOMORPHOLOGICAL PECULIARITIES OF CHANGES AT PULPITIS, ACCOMPANIED BY RESORBTION OF DENSE DENTAL TISSUES - Yugov, V.K.; Skripnikova, T.P.; Bubliy, T.D. (World of Medicine and Biology, 2012)
Radiomorphological manifestations of pulpitis on the roengenograms is reflected by the direct signs - parts of lightening on the background of more dense tissues: inner resorbtion in the form of inner granuloma in the tooth cavity or dentine; inner caries; and outher resorbtion of the root.To the inndirect signs of pulpitis are refered: deep cariouses cavity and widening of periodontal fissure .